Case report: Environmental adjustment for visual hallucinations in dementia with Lewy bodies based on photo assessment of the living environment - Ishimaru, Daiki; Kanemoto, Hideki; Hotta, Maki; Nagata, Yuma; Koizumi, Fuyuki; Satake, Yuto; Taomoto, Daiki; Ikeda, Manabu (Frontiers in Psychiatry, 2024)
Background: Visual hallucinations (VH) are associated with visual prediction error in patients with dementia with Lewy bodies (DLB). Given this relationship, environmental adjustments have been suggested, but detailed contents for implementing such environmental adjustments and assessments are poorly documented. This case report preliminarily demonstrates methods for improving VH through our experience with two patients with DLB. We conducted familial interviews to assess the phenomenological features of VH and reviewed photographs of patients' homes to identify the environmental triggers of VH, known as photo assessment of the living environment (PA-LE).Case Description: Patient 1 was a 78-year-old woman with a Mini-Mental State Examination (MMSE) score of 11/30. She experienced seeing a stranger, children, and cats at home, which frightened her. VH frequently occurred in the living room and bedroom. The PA-LE showed that several environmental features, such as cushions on a sofa, the pattern on a carpet under a table, and clothing on hangers, were suggestive triggers of VH.Patient 2 was an 88-year-old woman with a MMSE score of 5/30. She had seen strangers, children, and animals at home, some of which were linked to a theft delusion. VH frequently occurred in the living room and bedroom. The PA-LE found that several environmental features, such as clothing on hangers and dolls, were suggestive of VH triggers. Non-pharmacological approaches were tailored to the patients' environmental and psychological states using interviews and PA-LE. This included removing environmental triggers, reducing negative mood, and providing coping strategies for VH. This improved their VH and their caregivers' knowledge of VH.Phenomenological assessments using photographs of the patient's home could identify the environmental triggers associated with VH in patients with DLB and assist in environmental adjustments.